Cytotoxicity and anti-inflammatory properties of a GLP-1 receptor agonist in a model of human peripheral blood mononuclear cell culture - Marija Drakul; Vanja Mališ; Sara Rakočević; Ljiljana Kozić; Darinka Popović; Anđela Mandić; Miodrag Colic (Биомедицинска истраживања, 2024)
Introduction: GLP-1R agonists (GLP-1RAs) are a type of anti-hyperglycemic medications used for the management of type 2 diabetes mellitus (T2DM). In addition to glucose-lowering effects, GLP-1R agonists (GLP-1RAs) also provide further advantages by promoting weight loss and controlling blood pressure. Furthermore, GLP-1RAs have been reported for their therapeutic benefits in neurological, cardiovascular, endocrine, and metabolic diseases. Emerging evidence from many clinical and experimental studies, as well as in vitro researches, suggests that GLP-1RA agonists may reduce inflamma tion and modify the immunological response, but the underlying molecu lar mechanisms remain unclear. In this research, we examined the effect of GLP-1RA on the cytotoxicity, proliferative activity, and cytokine production of human peripheral blood mononuclear cells (PBMCs) in vitro. Methods: The peripheral blood mononuclear cells (PBMCs) cultures from healthy volunteers were used. GLP-1RA (DMB), in different concentrations, was added to the cell cultures. A flow cytometry assay was used to assess cell viability, while MTT and CFSE dye dilution assays were used to quantify proliferative activity. Cytokine levels were measured using a sandwich en zyme-linked immunosorbent assay (ELISA). Results: The cytotoxicity data demonstrated that only the highest DMB concentration (1000 nM) decreased the metabolic activity (viability) of PBMCs (p<0.05) in comparison to untreated cultures, while concentra tions of 200 nM (p<0.05) and 1000 nM (p<0.001) of GLP-1RA increased the proportion of late apoptotic and necrotic cells (p<0.001). The prolif eration of PBMCs was significantly decreased in the presence of GLP-1RA at a 100 nM concentration when compared to the control (p<0.05). The same concentration of GLP-1RA significantly reduced the production of IL-6, IL-1?, and TNF-?. Conclusion: Our results suggested that GLP-1RA (DMB), at a non-toxic concentration of 100 nM, inhibited the proliferation and production of pro-inflammatory cytokines by human PBMCs in vitro. These findings open the perspective to study the immune response in detail in future experiments.
Keywords: apoptosis; necrosis; GLP-1; anti-hyperglycemic agents; proliferation; cytokines